Race Meets Bargaining in Product Development - Emin Karagözoglu; Kerim Keskin; Cagri Saglam (Center for Economic Studies and ifo Institute (CESifo), 2020)
We introduce a model of product development in a firm. Our model describes the process as a multi-stage contest (i.e., race) with an endogenous length (with one stage or two stages) between two workers. We model the payments to workers from the new product using the normatively appealing Nash bargaining solution (see Nash, 1950). In our model the disagreement payoffs endogenously depend on the contest outcome. More precisely, a bargaining advantage is given to the leading worker in the product development contest. We analytically characterize subgame perfect equilibrium effort levels of workers and describe the conditions under which a full-edged final (as opposed to, say, a prototype) product is developed. Our comparative static analyses reveal economically intuitive insights. Finally, we provide an answer to the firm's problem of optimal incentive provision (considering both collective and individual incentives).
Keywords: C72; C78; D86; O31; O32; 330; product development; contests; Nash bargaining solution; optimal contracts; subgame perfect Nash equilibrium; race